Issue of colorectal cancer at the beginning of XXI century: achievements and prospects - O. I. Kit (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze publications devoted to significant advances in treatment of colorectal cancer.Key points. Essential successes in colorectal cancer treatment are determined: improvement of surgical technique, performance of total mesorectumectomy and expanded lymph node dissections, application of staplers at anterior rectectomy, laparoscopic surgery, improvement of radiation technique and its integration with chemotherapy, development and introduction of new chemotherapeutic agents, application of targeted therapy. Existing problems in treatment of colorectal cancer are determined: low rate of early stage detection, investigation and treatment of cancer patients by non-oncologist doctors, wide promotion of alternative medicine methods by mass media.Conclusion. The further introduction of scientific advances in clinical practice, modernization of public health services will promote new achievements in treatment of colorectal cancer.